Pharmacokinetic/pharmacodynamic considerations for new and current therapeutic drugs for uncomplicated gonorrhoea—challenges and opportunities. (December 2020) - Theuretzbacher, Ursula; Barbee, Lindley; Connolly, Kristie; Drusano, George; Fernandes, Prabha; Hook, Edward; Jerse, Ann; O'Donnell, John; Unemo, Magnus; Van Bambeke, Françoise; VanScoy, Brian; Warn, Peter; et al.
Abstract: Background: Increasing multidrug resistance rates in Neisseria gonorrhoeae have raised concerns and an urgent call for new antibiotics for treatment of gonorrhoea. Several decades of subdued drug development in this field and the recent failures of two new antibiotics to show non-inferiority compared with the current first-line antibiotics ceftriaxone plus azithromycin highlight the need for improved preclinical tools to predict clinical outcome of new drugs in the development process. Objectives: To summarize current pharmacokinetic/pharmacodynamic (PK/PD) knowledge and dose-finding strategies for antibiotics against gonorrhoea. Sources: Literature review of published papers and discussions by global experts at a special workshop on this topic. Content: We review current knowledge of gonococcal specific PK/PD principles and provide an update on new in vitro and in vivo models to correlate drug exposure with clinical outcome, and identify challenges and gaps in gonococcal therapeutic research. Implications: Identifying the ideal antimicrobial agent and dose for treating uncomplicated urogenital and pharyngeal gonococcal disease requires appropriate validated non-clinical PK/PD models. Recent advances in adapting in vitro and in vivo models for use in gonorrhoea are an important step for enabling the development of new drugs with reduced risk of failure in Phase 3 clinical development and diminish the risk of emergence of resistance.